Contribution of the efflux pump AcrAB-TolC to the tolerance of chlorhexidine and other biocides in Klebsiella spp. Issue 3 (24th March 2022) - Wand, Matthew E.; Darby, Elizabeth M.; Blair, Jessica M. A.; Sutton, J. Mark
Abstract : Introduction. We are becoming increasingly reliant on the effectiveness of biocides to combat the spread of Gram-negative multi-drug-resistant (MDR) pathogens, including Klebsiella pneumoniae . It has been shown that chlorhexidine exposure can lead to mutations in the efflux pump repressor regulators SmvR and RamR, but the contribution of each individual efflux pump to biocide tolerance is unknown. Hypothesis. Multiple efflux pumps, including SmvA and AcrAB-TolC, are involved in increased tolerance to biocides. However, strains with upregulated AcrAB-TolC caused by biocide exposure are more problematic due to their increased MDR phenotype. Aim. To investigate the role of AcrAB-TolC in the tolerance to several biocides, including chlorhexidine, and the potential threat of cross-resistance to antibiotics through increased expression of this efflux pump. Methodology. Antimicrobial susceptibility testing was performed on K. pneumoniae isolates with ramR mutations selected for after exposure to chlorhexidine, as well as transposon mutants in components and regulators of AcrAB-TolC. RTPCR was used to detect the expression levels of this pump after biocide exposure. Strains from the globally important ST258 clade were compared for genetic differences in acrAB -TolC and its regulators and for phenotypic differences in antimicrobial susceptibility. Results. Cross-resistance to antimicrobials was observed following mutations in ramR . Exposure to chlorhexidine led to increased expression of acrA and its activator ramA, and transposon mutants in AcrAB-TolC have increased susceptibility to several biocides, including chlorhexidine. Variations in ramR within the ST258 clade led to an increase in tolerance to certain biocides, although this was strain dependent. One strain, MKP103, that had increased levels of biocide tolerance showed a unique mutation in ramR that was reflected in enhanced expression of acrA and ramA . MKP103 transposon variants were able to further enhance their tolerance to specific biocides with mutations affecting SmvA. Conclusions. Biocide tolerance in K. pneumoniae is dependent upon several components, with increased efflux through AcrAB-TolC being an important one.